2019
DOI: 10.1002/solr.201900225
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering via Sputtered Oxygenated CdS:O Window Layer for Highly Efficient Sb2Se3 Thin‐Film Solar Cells with Efficiency Above 7%

Abstract: Antimony chalcogenide Sb2Se3 is an emerging photovoltaic absorber due to its appropriate bandgap (≈1.1 eV), high absorption coefficient (>105 cm−1), suitable p‐type conductivity, low toxicity, earth abundance, and excellent stability. However, the stringent growth condition and low photovoltage limit its power conversion efficiency (PCE). Herein, via a combined theoretical and experimental study, interface engineering via an oxygenated cadmium sulfide (CdS) window layer (CdS:O) is found to be an effective appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Furthermore, Guo et al found interestingly that the oxygenated CdS:O window layer can efficiently improve the efficiency of Sb 2 Se 3 solar cell, and the oxygen is accumulated at the interface between CdS:O and Sb 2 Se 3 layers . Their calculations showed that O Se has very low formation energy, similar to O S in Sb 2 S 3 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Guo et al found interestingly that the oxygenated CdS:O window layer can efficiently improve the efficiency of Sb 2 Se 3 solar cell, and the oxygen is accumulated at the interface between CdS:O and Sb 2 Se 3 layers . Their calculations showed that O Se has very low formation energy, similar to O S in Sb 2 S 3 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We can find that the MXene‐derived device in our work is the first time to join the club of over 8% efficiency using the noble metal and/or organic‐free BCMs for Sb 2 (S x Se 1− x ) 3 solar cells. [ 10–13,15,56–64 ] This back contact engineering strategy, via the novel, stable, and eco‐friendly BCMs of MXene electrode, enables to achieve a low‐cost and full‐inorganic Sb 2 (S,Se) 3 solar cell with high efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was introduced by applying a CdS:O ETL for Sb 2 Se 3 solar cells, and the CdS:O layer was deposited by a sputtering method. [74] The sputtered oxygenated CdS ETL to the interstitial sites in the vdW gap, which facilitated the formation of Sb-O-Se chain. [75]…”
Section: Composition Engineeringmentioning
confidence: 99%
“…A similar approach was introduced by applying a CdS:O ETL for Sb 2 Se 3 solar cells, and the CdS:O layer was deposited by a sputtering method. [ 74 ] The sputtered oxygenated CdS:O ETL provided a well‐matched band alignment with the Sb 2 Se 3 absorber, leading to a higher V OC . More importantly, the oxygen in CdS:O can not only effectively passivate the vdW gap of Sb 2 Se 3 but also tailor the (Sb 4 Se 6 ) n ribbons to (221)‐textured orientation.…”
Section: Band Alignment Optimizationmentioning
confidence: 99%